2014
DOI: 10.17557/tjfc.43607
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological and Forage Quality Traits of Selected Alfalfa Populations and Their Application in Breeding

Abstract: The objectives of this research were to evaluate agro-morphological and forage quality performances of selected alfalfa populations and to predict the genetic potential of this populations as a source of the material for breeding programs and/or commercial use. Twenty selected alfalfa populations and two control cultivars were tested over three consecutive years (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
4
17
4
Order By: Relevance
“…These * L: lignin; CP: crude protein; IVDMD: in vitro dry matter digestibility; NDF: neutral detergent fiber; ADF: acid detergent fiber; SLR: stem/leaf ratio; CVe (%): coefficient of experimental variation; CVg (%): coefficient of genetic variation. values were higher than those found by Costa et al (2006) and Vasconcelos et al (2010), and represent optimum values. Except for the first cut, heritability estimates for this trait were high, indicating a high relation between phenotypic and genotypic values.…”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…These * L: lignin; CP: crude protein; IVDMD: in vitro dry matter digestibility; NDF: neutral detergent fiber; ADF: acid detergent fiber; SLR: stem/leaf ratio; CVe (%): coefficient of experimental variation; CVg (%): coefficient of genetic variation. values were higher than those found by Costa et al (2006) and Vasconcelos et al (2010), and represent optimum values. Except for the first cut, heritability estimates for this trait were high, indicating a high relation between phenotypic and genotypic values.…”
Section: Resultscontrasting
confidence: 54%
“…Since most alfalfa traits exhibit a complex genetic control (Milic et al 2014, Li et al 2015, simultaneous selection has been used, since it maximizes the chances of success in the breeding process by providing balanced gains to all traits, making it possible to obtain gains even for unfavorably correlated traits (Cruz et al 2014). Vasconcelos et al (2010) found higher gains for alfalfa traits selection, when applying direct selection. However, this selection led to an increase in the susceptibility of the cultivars, in relation to diseases incidence.…”
Section: Abstract Resumomentioning
confidence: 88%
See 2 more Smart Citations
“…Avci et al (2010) recorded significant differences among alfalfa lines and cultivars in dry matter yield and quality traits. Agro-morphological traits have been used to classify and study the genetic diversity in alfalfa germplasm collections (Tucak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%